Down-regulation of SlIAA15 in tomato altered stem xylem development and production of volatile compounds in leaf exudates - Deng, Wei (Landes Bioscience, 2012)
The Aux/IAA family genes encode short-lived nuclear proteins that function as transcriptional regulators in auxin signal transduction. Aux/IAA genes have been reported to control many processes of plant development. Our recent study showed that down-regulation of SlIAA15 in tomato reduced apical dominance, altered pattern of axillary shoot development, increased lateral root formation and leaves thickness. The SlIAA15 suppressed lines display strong reduction of trichome density, suggesting that SlIAA15 is involved in trichome formation. Here, we reported that SlIAA15-suppressed transgenic lines display increased number of xylem cells compared to wild-type plants. Moreover, the monoterpene content in trichome exudates are significantly reduced in SlIAA15 down-regulated leaves. The results provide the roles of SlIAA15 in production of volatile compounds in leaf exudates and xylem development, clearly indicating that members of the Aux/IAA gene family can play distinct and specific functions.